Wheat cultivars affecting life history and digestive amylolytic activity of Sitotroga cerealella Olivier (Lepidoptera: Gelechiidae). Issue 4 (28th March 2016) - Borzoui, E.; Naseri, B.
Abstract: The life history and digestive α-amylase activity of the Angoumois grain moth, Sitotroga cerealella Olivier (Lepidoptera: Gelechiidae) were studied on six wheat cultivars (Arg, Bam, Nai 60, Pishtaz, Sepahan and Shanghai) at 25 ± 1°C, relative humidity of 65 ± 5% and a photoperiod of 16:8 (L:D) h. A delay in the developmental time of S. cerealella immature stages was detected when larvae were fed on cultivar Sepahan. The maximum survival rate of immature stages was seen on cultivar Bam (93.33 ± 2.10%), and the minimum rates were on cultivars Nai 60 (54.66 ± 2.49%) and Sepahan (49.33 ± 4.52%). The highest realized fecundity and fertility were recorded for females which came from larvae fed on cultivar Bam (93.30 ± 2.10 eggs/female and 91.90 ± 3.10%, respectively); and the lowest ones were observed for females which came from larvae fed on cultivar Sepahan (49.30 ± 4.50 eggs/female and 67.4 ± 11.1%, respectively). The heaviest male and female weights of S. cerealella were observed on cultivar Bam (2.97 ± 0.02 and 4.80 ± 0.01 mg, respectively). The highest amylolytic activity of the fourth instar was detected on cultivar Bam (0.89 ± 0.04 mg maltose min −1 ), which had the maximum mean hundred-wheat weight (5.92 ± 0.19 g). One α-amylase isozyme was detected in the midgut extracts from the fourth instar larvae fed on different wheat cultivars, and the highest intensity was found in larvae fed on cultivar Bam. Correlation analyses showed that very high correlations existed between the immature period, fecundity and fertility on one side and inhibition of α-amylase, soluble starch content and hundred-wheat weight on the other. According to the obtained results, cultivar Sepahan is an unfavorable host for the feeding and development of S. cerealella .